2022
DOI: 10.1109/access.2022.3195039
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Defect Prediction Based on Federated Reinforcement Learning via Gradient Clustering

Abstract: Heterogeneous defect prediction (HDP) refers to using heterogeneous data collected by other projects to build a defect prediction model to predict the software modules prone to defects in a project. Traditional methods usually involve the measurement of the source project and the target project. However, due to the limitations of laws and regulations, these original data are generally not easy to obtain, which forms a data island. As a new machine learning paradigm, federated learning (FL) has great advantages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Madi et al [41] proposed a secure framework relying on Homomorphic Encryption and Verifiable Computation, and conducted experiments on the FEMNIST dataset. Wang et al [42] proposed a federated reinforcement learning method based on gradient clustering (FRLGC). FRLGC adds Gaussian noise to the data of local clients to achieve data level privacy protection.…”
Section: B Federated Learningmentioning
confidence: 99%
“…Madi et al [41] proposed a secure framework relying on Homomorphic Encryption and Verifiable Computation, and conducted experiments on the FEMNIST dataset. Wang et al [42] proposed a federated reinforcement learning method based on gradient clustering (FRLGC). FRLGC adds Gaussian noise to the data of local clients to achieve data level privacy protection.…”
Section: B Federated Learningmentioning
confidence: 99%
“…The authors of [32] developed a flexible cluster federated learning framework that divides client clusters based on the similarity between edge model training directions and experimentally demonstrated that the model accuracy outperforms that of traditional FL systems. To address the interference of distributed heterogeneous environments on the prediction of defects, the authors in [33] proposed a FL framework based on model clustering by clustering encrypted model gradients to create suitable clusters and validated the framework with several open datasets. The results showed that the algorithm outperformed the related defect prediction algorithm.…”
Section: Related Workmentioning
confidence: 99%
“…Experiments on the open-source software defect prediction dataset showed that this method improves the performance of the model, greatly reduced the impact of low-quality data on the model, and enhanced the robustness of the model. Wang et al proposed federated reinforcement learning via gradient clustering (FRLGC) [12] and verified that FRLGC is superior to the related cross-project software defect prediction methods in three public databases.…”
Section: Introductionmentioning
confidence: 99%